Age-related deficits in synaptic plasticity rescued by activating PKA or PKC in sensory neurons of Aplysia californica - Kempsell, Andrew T.; Fieber, Lynne A. (Frontiers in Aging Neuroscience, 2015)
Brain aging is associated with declines in synaptic function that contribute to memory loss, including reduced postsynaptic response to neurotransmitters and decreased neuronal excitability. To understand how aging affects memory in a simple neural circuit, we studied neuronal proxies of memory for sensitization in mature versus advanced age Aplysia. Glutamate- (L-Glu-) evoked excitatory currents were facilitated by the neuromodulator serotonin (5-HT) in sensory neurons (SN) isolated from mature but not aged animals. Activation of PKA and PKC signaling rescued facilitation of L-Glu currents in aged SN. Similarly, PKA and PKC activators restored increased excitability in aged tail SN. These results suggest that altered synaptic plasticity during aging involves defects in second messenger systems